Experiments on Pattern Language-Based Modeling - Braga, Rosana T. V.; Germano, Fernao S. R.; Masiero, Paulo Cesar (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2003: Anais do XVII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2003.23851, 2003)
The GRN pattern language can be used to guide the analysis of applications in the business resource management domain. The result is an analysis model for the application, showing the patterns applied to model it and allowing the use of a tool to automatically obtain the final application code. In this paper we describe a series of experiments conducted to evaluate the quality of the analysis models produced using the GRN pattern language compared to the analysis models produced by using an ad-hoc approach. Three experiments were performed with different kinds of subjects: undergraduate students, graduate students, and information technology professionals. The results have shown that the analysis models produced using the GRN pattern language have less errors than those produced using an ad-hoc system analysis approach.